Accuracy of clinical coding for procedures in oral and maxillofacial surgery. Issue 8 (October 2016) - Khurram, S.A.; Warner, C.; Henry, A.M.; Kumar, A.; Mohammed-Ali, R.I.
Abstract: Clinical coding has important financial implications, and discrepancies in the assigned codes can directly affect the funding of a department and hospital. Over the last few years, numerous oversights have been noticed in the coding of oral and maxillofacial (OMF) procedures. To establish the accuracy and completeness of coding, we retrospectively analysed the records of patients during two time periods: March to May 2009 (324 patients), and January to March 2014 (200 patients). Two investigators independently collected and analysed the data to ensure accuracy and remove bias. A large proportion of operations were not assigned all the relevant codes, and only 32% - 33% were correct in both cycles. To our knowledge, this is the first reported audit of clinical coding in OMFS, and it highlights serious shortcomings that have substantial financial implications. Better input by the surgical team and improved communication between the surgical and coding departments will improve accuracy.